Performing art traditional heritage : implementation of website to convey information of Wayang Kulit / Farrah 'Aini Hj Lugiman - Hj Lugiman, Farrah 'Aini (2005)
The problem of this study is to describe the characteristics of emblems as accessories for motorcycles particularly in the aspect of the design process, materials used, colours, shape and form, motifs, surface fmishing, size and placement. At the moment there is no proper documentation in relation to emblem development. This has caused difficulties for designers, students and manufacturers who want information for references. This study is confined to these eight areas and it is not intended to touch on other areas related to motorcycles. Data for this research was gathered through the use of observation and questionnaire. Researcher observes about 151 pieces ofemblems on the market. The questionnaire was divided into two parts, A and B. Part A was intended to gather information on the respondents while Part B contained eight sections, each related to the eight areas understudy. Every section contains between nine to twenty nine statements. There were eight experts selected as respondents. These respondents were motorcycle and emblem manufacturers. This research has reached the following findings. First, the design is an important aspect of the whole process of emblem development. Secondly, emblems are either made of metal or plastic, though plastic is more preferred than metal. Thirdly, manufacturers tend to use a common colour for their motorcycle emblems. Fourthly, emblems do not have a specific shape and fonn. Fifthly, brand names, models and corporate logos are primary motifs for emblems. Sixthly, the surface finishing is important for motorcycle emblems. Seventhly, emblems do not have a specific size. Lastly, emblems do have a specific location and as a decoration parts to be applied on motorcycles. An emblem is an important component in the manufacture of a motorcycle because its role is not only for aesthetical purposes but also for its corporate image ofthe company, trademark and identity for its product~ It is also used for effective marketing of the motorcycle. Because of its importance, motorcycle manufacturers must implement a systematic work system for emblem development to ensure a high quality in design and production.